2016
DOI: 10.1117/12.2233472
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low noise TES bolometer arrays for SAFARI instrument on SPICA

Abstract: SRON is developing ultra-low noise Transition Edge Sensors (TESs) based on a superconducting Ti/Au bilayer on a suspended SiN island with SiN legs for the SAFARI instrument aboard the SPICA mission. We successfully fabricated TESs with very narrow (0.5-0.7 µm) and thin (0.25 µm) SiN legs on different sizes of SiN islands using deep reactiveion etching process. The pixel size is 840×840 µm 2 and there are variety of designs with and without optical absorbers. For TESs without absorbers, we measured electrical N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…SAFARI's TES bolometers are two orders of magnitude more sensitive than bolometers used for ground-based observations [19] and testing them requires careful attention to stray-light protection and shielding from electrical, magnetic, and mechanical disturbances [20] . The detector requirements are within reach: we have demonstrated the required NEP≤2×10 -19 W/√Hz [21] and optical efficiency ≥50% for single detectors [22] . More recent optical measurements of arrays fabricated at the University of Cambridge are described elsewhere in these proceedings [23] .…”
Section: Focal-plane Assemblymentioning
confidence: 87%
“…SAFARI's TES bolometers are two orders of magnitude more sensitive than bolometers used for ground-based observations [19] and testing them requires careful attention to stray-light protection and shielding from electrical, magnetic, and mechanical disturbances [20] . The detector requirements are within reach: we have demonstrated the required NEP≤2×10 -19 W/√Hz [21] and optical efficiency ≥50% for single detectors [22] . More recent optical measurements of arrays fabricated at the University of Cambridge are described elsewhere in these proceedings [23] .…”
Section: Focal-plane Assemblymentioning
confidence: 87%
“…Finally, we note that the speed of TES bolometers may be a concern when pushed to the lowest NEPs, since fundamentally, the time constant scales as the thermal conductance G, and G must be reduced as the square of desired NEP improvements (NEP ∝ ffiffiffiffi G p ). Khosropanah et al 38 indicated time constants of 0.2 to 0.3 ms for their low-NEP devices, which indicates that 3 ms is possible at the NEP target for OSS.…”
Section: Detector Systemmentioning
confidence: 97%
“…These programs have demonstrated NEPs as low as 1 × 10 −19 W Hz −1∕2 at both Jet Propulsion Laboratory (JPL) and Space Research Organization of the Netherlands. 37,38 Pushing to lower NEPs is possible though potentially cumbersome: either base temperatures must be reduced from the canonical 50 mK, and/or the leg isolation needs to be improved with more exotic microfabricated structures. Another challenge with a TES system in light of the formats required for OSS is the complexity of focal plane assembly, in particular the hybridization with superconducting quantum interference devices (SQUIDs).…”
Section: Detector Systemmentioning
confidence: 99%
“…SAFARI employs the latest generation of ultra-sensitive TES to detect the incoming photons (Khosropanah et al 2016;Audley et al 2016;Suzuki et al 2016;Goldie et al 2012;Beyer et al 2012). TES bolometers fabricated at SRON (Ridder et al 2016) have already demonstrated the required NEP (Khosropanah et al 2016), as well as the required optical efficiency (Audley et al 2016). To achieve their performance, the detectors, their readout, and the first-stage amplifiers must be operated at 50-mK, which requires that both the sensors and the cold electronics be cooled and thermally isolated from the 1.8-K environment of the GM.…”
Section: The Safari Detector Grating Modulesmentioning
confidence: 99%